2023
DOI: 10.1039/d2ob02115c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-vinyl isothiocyanates and carbamates by the cleavage of NH-1,2,3-triazoles with one-carbon electrophiles

Abstract: Treament of NH-1,2,3-triazoles with one-carbon electrophiles, such as thiophosgene and triphosgene, led to N-vinylated ring cleavage products. Using this approach the synthesis of N-vinylisothiocyanates from NH-triazoles and thiophosgene was achieved....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The proposed mechanism is illustrated in In 2023, Beier et al reported the synthesis of vinyl isothiocyanates from NH-1,2,3-triazoles. 97 Although transformations involving the cleavage of N-substituted 1,2,3-triazoles are well established, much less attention has been paid to the ringcleavage chemistry of NH-1,2,3-triazoles. They transformed NH-1,2,3-triazoles via ring cleavage, using thiophosgenes or triphosgenes and nucleophiles.…”
Section: Recent Advances In Isothiocyanate Synthesis With Type Bmentioning
confidence: 99%
“…The proposed mechanism is illustrated in In 2023, Beier et al reported the synthesis of vinyl isothiocyanates from NH-1,2,3-triazoles. 97 Although transformations involving the cleavage of N-substituted 1,2,3-triazoles are well established, much less attention has been paid to the ringcleavage chemistry of NH-1,2,3-triazoles. They transformed NH-1,2,3-triazoles via ring cleavage, using thiophosgenes or triphosgenes and nucleophiles.…”
Section: Recent Advances In Isothiocyanate Synthesis With Type Bmentioning
confidence: 99%
“…Recently, one synthetic approach of N -vinyl isothiocyanate from triazole utilizing thiophosgene was reported by Motornov and Beier. 20 Although several isothiocyanation methods successfully provide alkenyl isothiocyanates, they require the preparation of alkenyl substrates as isothiocyanate precursors, thus, complicated synthetic routes are inevitable to obtain alkenyl isothiocyanates. In 1979, α-bromination of alkyl isothiocyanate under photo-irradiation conditions was reported.…”
mentioning
confidence: 99%
“…19 (Scheme 2B) Recently, one synthetic approach of N-vinyl isothiocyanate from triazole utilizing thiophosgene was reported by Motornov and Beier. 20 Although several isothiocyanation methods successfully provide alkenyl isothiocyanates, they require the preparation of alkenyl substrates as isothiocyanate precursors, thus, complicated synthetic routes are https://doi.org/10.26434/chemrxiv-2024-42j6j ORCID: https://orcid.org/0000-0001-5405-3069 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 inevitable to obtain alkenyl isothiocyanates.…”
mentioning
confidence: 99%